Mathematics anxiety and teaching styles among mathematics teachers in public senior high school in Padang West Sumatera Indonesia - Hasmaida, Wela (Kulliyyah of Education, International Islamic University Malaysia, 2016)
Mathematics anxiety is like a cycle (Puteh, 2002). Teachers who had bad experiences with their mathematics teachers in the past might influence their current students in learning mathematics. The purpose of this study is to investigate the relationship between mathematics anxiety and teaching styles among mathematics teachers in Public Senior High Schools in Padang, West Sumatera Indonesia. Besides, this study aims to indentify the level of mathematics anxiety among mathematics teachers, to investigate variation of mathematics teachers' level of mathematics anxiety based on their gender, age, and number of years of teaching experiences. The quantitative method is used. Two sets of questionnaire are distributed to 102 mathematics teachers who are teaching in Public Senior High Schools in Padang, West Sumatera, Indonesia. The data is analyzed using the descriptive, independent t-test analysis, one-way ANOVA, and Chi-square. The findings from the study show that mathematics teachers of Public Senior High Schools in Padang experience low level of mathematics anxiety and there is no significant mean difference in mathematics teachers' level of mathematics anxiety with regards to gender, age, and number of years of teaching experiences. In addition, there is no relationship between mathematics anxiety and teaching styles. High level of mathematics anxiety will prevent the mathematics teachers to use teacher-centered approach in teaching process (Hembre, 1990).